Effect of Traditional Chinese Medicine collapse stains combined with western medicine in treating acute herpes zoster (中药溻渍联合西医治疗急性期带状疱疹的疗效观察) - YAO Meiyu (姚美玉); SUN Mingli (孙明丽); TANG Ling (唐玲); ZHOU Jie (周洁); CHEN Hong (陈宏) (Association of Integrative Nursing, 2022)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) collapse stains combined with western medicine in treating acute herpes zoster. Methods A total of 60 patients with acute herpes zoster were randomly divided into observation group and control group, with 30 cases in each group. The control group was treated with conventional western medicine, and the observation group was treated with TCM collapse stains combined with western medicine. The pain degree measured by Visual Analogue Scale (VAS) and treatment efficacy of the two groups were compared. Results The VAS score of both group decreased after treatment, and the VAS score in the observation group was significantly lower than that in the control group(P＜0. 05). The total effective rate of the observation group was 83. 33%(25/30), which was higher than 66. 67%(20/30) in the control group (P＜0. 05). Conclusion The Combination of TCM collapse stains and western medicine is more effective than single use of western medicine in relieving the pain and improve the clinical symptoms of patients with acute herpes zoster. (目的 探讨中药溻渍联合西医治疗急性期带状疱疹的临床效果。方法 选取2021年5月-2022年1月收治的急性期带状疱疹患者60例, 随机分为观察组和对照组, 各30例。对照组给予常规干预, 观察组在对照组基础上实施中药溻渍治疗。评估两组疼痛程度和临床疗效。结果 干预后, 两组视觉模拟评分法(VAS)评分均降低, 且观察组评分低于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率83. 33%(25/30), 高于对照组66. 67%(20/30), 差异有统计学意义(P＜0. 05)。结论 中药溻渍联合西医治疗急性期带状疱疹, 能有效减轻患者疼痛, 改善临床症状。)